THE ROLE OF TROPES IN THE CREATION OF ARTISTIC IMAGERY (Western European Journal of Linguistics and Education, 2024)
Tropes, as powerful tools of linguistic expression, play a key role in creating artistic imagery. They allow the author to go beyond the literal meaning of the word and create vivid, memorable images that evoke certain emotions and associations in the reader. This article is devoted to the study of the role of tropes in the formation of artistic imagery. The paper examines the concept of "imagery", the theoretical foundations of understanding tropes and their functions in creating artistic images.